Boy playing in the sand - Unknown:::Creator::::::::::::
Photograph shows a little boy, who appears to be Asian American, playing in the sand on the playground at the Villa Nueva child care center. He is holding a shovel and there is a bucket filled with sand in front of him. The bucket is partially buried. There is a partially visible little girl, who appears to be African American, sitting with another bucket in the background.